Comparing Freshman and doctoral engineering students in design: mapping with a descriptive framework - Marques, Pedro (2018)
This paper reports the results of a study of engineering students' approaches to an open-ended design problem. To carry out this, sketches and interviews were collected from 9 freshmen (first year) and 10 doctoral engineering students, when they designed solutions for orange squeezers. Sketches and interviews were analysed and mapped with a descriptive 'ideation framework' (IF) of the design process, to document and compare their design creativity (Carmona Marques, P., A. Silva, E. Henriques, and C. Magee. 2014. "A Descriptive Framework of the Design Process from a Dual Cognitive Engineering Perspective." International Journal of Design Creativity and Innovation 2 (3): 142-164). The results show that the designers worked in a manner largely consistent with the IF for generalisation and specialisation loops. Also, doctoral students produced more alternative solutions during the ideation process. In addition, compared to freshman, doctoral used the generalisation loop of the IF, working at higher levels of abstraction. The iterative nature of design is highlighted during this study - a potential contribution to decrease the gap between both groups in engineering education.